THE INFLUENCE OF POLITICAL AWARENESS ON POLITICAL PARTICIPATION OF FIRST-TIME VOTERS IN THE 2024 GENERAL ELECTIONS (PEMILU). - Jamal, Ode; Andhika L. Rahail, Joseph; Sopyan Hadi, Ade; Natalia Tecuari, Desi; Yuliana Tjoe , Ruth (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the extent to which political awareness influences political participation among first-time voters. The study used a quantitative approach with a correlational method. The sample was 124 first-time voters from a total population of 182 PPKn students from the Faculty of Teacher Training and Education, Cenderawasih University, who were selected using a purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using validity, reliability, Pearson correlation, and simple linear regression tests using SPSS 26. The results showed that the majority of respondents had a high to very high level of political awareness, as did their level of political participation. Statistical analysis showed a very strong relationship between political awareness and political participation (r = 0.826), with a significant positive effect of 68.2%. Based on the research results, it can be concluded that the higher the political awareness of first-time voters, the higher their participation in elections. Political awareness is a key factor driving the involvement of the younger generation in the democratic process. Therefore, first-time voters are expected to be more active and critical in determining their political choices, while political parties and prospective leaders need to convey clear, transparent, and educational political messages. Furthermore, educational institutions play a strategic role in fostering students' political awareness as part of civic education, thereby shaping a generation that is critical, participatory, and responsible for the future of Indonesian democracy.